2014
DOI: 10.1186/1475-2875-13-47
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to assess community barriers to malaria mass drug administration trials in the Gambia

Abstract: BackgroundMass drug administration (MDA) is a strategy widely used in the control of human parasitic diseases but has been rarely attempted with malaria, the most common and dangerous parasitic disease in humans. MDA is an intervention strategy that involves simultaneously dispensing treatment to an entire population in a given geographic area. With some areas in sub-Saharan Africa documenting a decline in malaria transmission, the feasibility of MDA to further reduce malaria transmission is being considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 24 publications
7
57
1
Order By: Relevance
“…The post-MDA survey findings showed that the reasons for failure to complete the ACT doses were fear of side-effects such as abdominal pain, headaches, vomiting, dizziness, sneezing, muscular aches, fever, nausea and body malaise. Similar findings were observed in studies conducted in The Gambia where barriers of the MDA campaign included the perception and fear of the community members on the side-effects of the drugs and procedures [ 20 , 21 ]. These misconceptions by the participants and misunderstandings about the medication can contribute greatly to the lack of adherence to an MDA [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…The post-MDA survey findings showed that the reasons for failure to complete the ACT doses were fear of side-effects such as abdominal pain, headaches, vomiting, dizziness, sneezing, muscular aches, fever, nausea and body malaise. Similar findings were observed in studies conducted in The Gambia where barriers of the MDA campaign included the perception and fear of the community members on the side-effects of the drugs and procedures [ 20 , 21 ]. These misconceptions by the participants and misunderstandings about the medication can contribute greatly to the lack of adherence to an MDA [ 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our study also highlights the need for contextually-relevant community engagement strategies, which appear to be vital to uptake by promoting trust and demand. The importance of community engagement activities has been widely referenced in previous studies on MDAs for a number of diseases including malaria, schistosomiasis, and LF [25][26][27]. Beyond the well-documented need to address prevailing rumors and generate demand through imparting knowledge about the infection, our results indicate that community engagement can benefit both reach and uptake.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 49%
“…There the researchers found travel, perceived adverse drug reactions and rumours, inconveniences related to the logistics of MDA (e.g. waiting times) and the perceived lack of information about MDA were critical reasons for non-participation [17, 21, 22]. While the research into factors related to the participation in mass administrations of anti-malarial drugs is somewhat limited there is a broad experience how to engage communities in other biomedical interventions including interventions against the transmission of HIV, tuberculosis, and vector-borne disease [23].…”
Section: Discussionmentioning
confidence: 99%